(untitled) (Foro de Educacion, 2013)
This paper focuses on the historical and contemporary validity that John Dewey’s experience theory has had at the United States pedagogy. We analyze the context in which Dewey has developed his theoretical approach. We also point out against whom opposed his educational proposal based on the concept of learning by doing. In order to do that, we fit his philosophy inside of pragmatism and, in particular, within the instrumentalism. Moreover, we highlight the historical significance to the pedagogy of the concepts developed by Dewey: activity and experience as well as the implications that they have had for institutionalized education. Finally, we argue some of the issues that are discussed by the contemporary pedagogical debate arising from the premises of the experience theory